THE EFFECT OF TRADISIONAL MUSIC “CILOKAQ” THERAPY FOR THE ANXIETY LEVEL IN ELDERLY WOMEN AT THE RETIERMENT HOME - Harlina Putri Rusiana; Sopian Halid; Elisa Oktaviana; Rias Pratiwi Syafitri; Dewi Nur Sukma Purqoti; Fitri Romadonika; Ade Mely Rosmiatun (Universitas STRADA Indonesia, 2023)
Background: Elderly is who’s over 60 years old with decline in biological, psychological, social, and economic changes. Method: The design of this research is Pre-Experimental with One-Group Pretest-Posttest design with 30 respondents. Results: of this study used the chi square test with p value 0.002 <0.005, which means that there is an effect of cilokaq music therapy on the level of anxiety in the elderly. Conclution: Cilokaq music therapy can be used as an alternative to professional nursing actions for the elderly who experience anxiety and can be applied institutionally in the form of establishing permanent work procedures.